Inventory Management Model for Reducing Stockout rate by Applying Lean Warehousing and DDMRP Tools in a SMEs in the Commercial Sector - Gonzales León, Luis Martín (2023)
This case study addresses the problem of stock-outs and purchase planning, which represent the greatest impact on the economic loss for the company studied. For the analysis of the problem and the proposal approach, a focus was made on the main products sold, the Value Stream Mapping tool was used for the process analysis and the analysis of the main causes by means of Pareto diagrams and the Systematic Interrogation Technique. The implementation of the 5S methodology is proposed hand in hand with the Visual Management to have a better control of the stock and improve the workflow, in addition, the purchase planning is proposed from the application of the DDMRP tool with the objective of being able to meet the demand and have lower losses due to expiration of products. Finally, through the application and simulation of the proposed tools, an average reduction of 28.3% in warehouse ordering times and 25% in order preparation times is evidenced, likewise the DDMRP tool shows a reduction of stock breakage, managing to cover 100% of the demand.